Biological and Bioelectrochemical Systems for Hydrogen Production and Carbon Fixation Using Purple Phototrophic Bacteria - Vasiliadou, Ioanna A.; Berná, Antonio; Manchon, Carlos; Melero, Juan A.; Martinez, Fernando; Esteve-Nuñez, Abraham; Puyol, Daniel (Frontiers in Energy Research, 2018)
Domestic and industrial wastewaters contain organic substrates and nutrients that can be recovered instead of being dissipated by emerging efficient technologies. The aim of this study was to promote bio-hydrogen production and carbon fixation using a mixed culture of purple phototrophic bacteria (PPB) that use infrared radiation in presence or absence of an electrode as electron donor. In order to evaluate the hydrogen production under electrode-free conditions, batch experiments were conducted using different nitrogen (NH4Cl, Na-glutamate, N2 gas) and carbon sources (malic-, butyric-, acetic- acids) under various COD:N ratios. Results suggested that the efficiency of PPB to produce biogenic H2 was highly dependent on the substrates used. The maximum hydrogen production (H2_max, 423 mLH2/L) and production rate (H2_rate, 2.71 mLH2/Lh) were achieved using malic acid and Na-glutamate at a COD:N ratio of 100:15. Under these optimum conditions, a significant fixation of nitrogen in form of single-cell proteins (874.4 mg/L) was also detected. Under bio-electrochemical conditions using a H-cell bio-electrochemical device, the PPB were grown planktonic in the bio-cathode chamber with the optimum substrate ratio of malic acid and Na-glutamate. A redox potential of -0.5 V (vs Ag/AgCl) under bio-electrochemical conditions produced comparable amounts of bio-hydrogen but significantly negligible traces of CO2 as compared to the biological system (11.8 mLCO2/L). This suggests that PPB can interact with the cathode to extract electrons for further CO2 re-fixation (coming from the TCA cycle) into the Calvin cycle, thereby improving the C usage. It has also been observed during cyclic voltammograms that a redox potential of -0.8 V favours considerably the electrons consumption by the PPB culture, suggesting that the PPB can use these electrons to increase the biohydrogen production. These results are expected to prove the feasibility of stimulating PPB through bio-electrochemical processes in the production of H2 from wastewater resources, which is a field of special novelty and still unexplored.